Pengaruh Loan To Deposit Ratio, Capital Adequacy Ratio, Dan Non Performing Loan Terhadap Profitabilitas Perbankan Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Fanesha Fanesha; Nusa Muktiadji; Ganjar Hendrian (Jurnal Ilmiah Manajemen Kesatuan, 2021)
This study aims to determine how the influence of Loan to Deposit Ratio, Capital Adequacy Ratio and Non Performing Loans on Banking Profitability Listed on the Indonesia Stock Exchange (IDX) that occurs at PT Bank Central Asia Tbk, PT Bank Rakyat Indonesia (Persero) Tbk, PT Bank Mandiri (Persero) Tbk, PT Bank CIMB Niaga Tbk, PT Bank Negara Indonesia (Persero) Tbk, PT Bank Tabungan Negara (Persero) in 2014-2018. The data used in this study are quantitative data with secondary data sources derived from the financial statements of each bank. This research uses descriptive statistical analysis methods, inference analysis, classic assumption test, multiple linear analysis and coefficient of determination. Regression analysis is used to find out how the influence of independent variables on the dependent variable with a significance value of 5 percent. While the determination coefficient analysis is used to determine the relationship between the independent variable and the dependent variable. From the partial hypothesis test (T Test) that has been done by the author, it is obtained that the Loan to Deposit Ratio affects Return On Assets, Capital Adequacy Ratio has no effect on Return On Assets and Non Performing Loans has no effect on Return On Assets. For simultaneous hypothesis testing (Test F), the results obtained are that the independent variables namely Loan to Deposit Ratio, Capital Adequacy Ratio and Non Performing Loans simultaneously influence the Return on Assets. Key words : Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Return On Asset (ROA).